Intra-amygdalar okadaic acid enhances conditioned taste aversion learning and CREB phosphorylation in rats - Oberbeck, Denesa L. (2010)
Protein phosphatases (PPs) regulate many substrates implicated in learning and memory. Conditioned taste aversion (CTA) learning, in which animals associate a novel taste paired with a toxin and subsequently avoid the taste, is dependent on several serine/threonine phosphatase substrates and the PP1-binding protein spinophilin. In order to examine the effects of PP1/2A blockade on CTA acquisition and extinction, rats received bilateral infusions of okadaic acid (OA) (100 nM, 1 μl/hemisphere) or vehicle (0.15M NaCl) into the amygdala either 5 min prior to, or 5 min after, a single pairing of sodium saccharin (0.125%, 10-min access) and LiCl or NaCl (0.15M, 3 ml/kg i.p.). Two-bottle, 24-h preference tests were conducted for 13 days to measure CTA expression and extinction. Rats conditioned with saccharin and LiCl showed a decreased preference for saccharin, and OA administered before (but not after) the pairing of saccharin and LiCl resulted in a significantly stronger CTA that did not extinguish over 13 days. The enhancement of the CTA was not due to aversive effects of OA, because rats given OA and a pairing of saccharin and NaCl did not acquire a CTA. Finally, OA administration increased levels of phosphorylated CREB immunoreactivity following a CTA trial. Together, these results suggest a critical role for PP1/2A during normal CTA learning. Because CTA learning was enhanced only when OA was given prior to conditioning, phosphatase activity may be a constraint on learning during the taste-toxin interval but not during acquisition and consolidation processes that occur after toxin administration.